Ancient perspectives on Aristotle's De anima - Riel, Gerd van; Destrée, Pierre; Crawford, Cyril K.; Campe, Leen van (Ancient and medieval philosophy., 2009)
Aristotle's treatise "On the Soul" figures among the most influential texts in the intellectual history of the West. It is the first systematic treatise on the nature and functioning of the human soul, presenting Aristotle's authoritative analyses of, among others, sense perception, imagination, memory, and intellect. The ongoing debates on this difficult work continue the commentary tradition that dates back to antiquity. This volume offers a selection of papers by distinguished scholars, exploring the ancient perspectives on Aristotle's "De anima", from Aristotle's earliest successors through the Aristotelian Commentators at the end of Antiquity. It constitutes a twin publication with a volume entitled "Medieval Perspectives on Aristotle's "De anima"".